Principal's Strategy in Developing Student’s Discipline - Andrias Andrias; Yoga Anjas Pratama; Rinovian Rais; Muwahidah Nurhasanah; Afif Alfiyanto (Lectura : Jurnal Pendidikan, 2022)
The purpose of this study was to determine the principal's strategy in fostering student discipline at 23 Palembang Junior High Schools and what are the supporting and inhibiting factors. This study uses a qualitative method. Informants in this study were principals, vice principals, teachers, students, and the community—data collection techniques through observation, interviews, and documentation methods. The data analysis technique uses data reduction, data presentation, verification, and checking of the validity of the data. The results showed that the principal in fostering student discipline at 23 Palembang Junior High Schools had several strategies, namely 1) the existence of clear disciplinary rules; 2) providing an excellent example to students; 3) providing coaching; 4) communication with parents of students, and 5) give sanctions to students who violate the rules of school rules.